2020
DOI: 10.12659/msm.924325
|View full text |Cite
|
Sign up to set email alerts
|

Three‑Dimensional Ultrasonography in Preoperative and Postoperative Volume Assessment of the Undescended Testicle

Abstract: Background Ultrasound (US) is the preferred imaging method for cryptorchidism, but most guidelines indicate that its value is questionable. The aim of this study was to evaluate the clinical value of ultrasonic mobility and testicular atrophy index (TAI) based on three-dimensional US (3DUS) in preoperative and postoperative assessment of the undescended testis. Material/Methods Data from 158 children with unilateral extraperitoneal cryptorchidism were collected and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Compared with 2DUS volume, 3DUS volume were significantly smaller and had a narrower 95% LOA. It suggested that volume measured by 2DUS was overestimated, and volume measured by 3DUS was more reliable than those obtained by 2DUS, which was consistent with previous studies [ 21 , 25 , 26 ]. These results can be explained by the different measurement methods of the two modalities.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with 2DUS volume, 3DUS volume were significantly smaller and had a narrower 95% LOA. It suggested that volume measured by 2DUS was overestimated, and volume measured by 3DUS was more reliable than those obtained by 2DUS, which was consistent with previous studies [ 21 , 25 , 26 ]. These results can be explained by the different measurement methods of the two modalities.…”
Section: Discussionsupporting
confidence: 90%
“…However, TAI has been reported to differ in unilateral cryptorchid boys younger than 1 year of age compared to those older than 1 year of age. 2 The difference in the present study lies in the analysis of the correlation between TAI and age in boys with a unilateral cryptorchid testis, and then the difference of the above correlation is found between 6–24 months and 25–53 months.…”
Section: Discussionmentioning
confidence: 54%
“… 10 The TAIs of cryptorchid testes were calculated as follows: TAI = (contralateral testis volume − affected testis volume)/contralateral testis volume. 2 8 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers believe that although diagnostic imaging plays a limited role in the routine evaluation of most children with cryptorchidism, ultrasonography can help to identify the possible Mullerian structures in children with sexual development disorders or hypospadias complicated with cryptorchidism. In 2020, You et al ( 21 ) reported a study on the clinical value of measuring ultrasonic activity and the testicular atrophy index (TAI) by three-dimensional ultrasound imaging in the pre-operative and post-operative evaluation of cryptorchidism. The results showed that the TAI can objectively reflect the recovery of testicular volume after cryptorchidism surgery, and the evaluation of ultrasonic activity is helpful for the clinical treatment of the disease.…”
Section: Diagnosis Of Cryptorchidismmentioning
confidence: 99%